PROCESSING SAWLOGS INTO PARQUET BLANKS - Stamenkoska, Ana Marija; Rabadziski, Branko; Zlateski, Goran; Trposki, Zoran; Temelkova, Anastasija; Koljozov, Vladimir (Innovation in Woodworking Industry and Engineering design, 2024)
rizontal plane. A parquet strip is the principal constructional element of the parquet. This wooden strip is obtained as a result of processing the flooring blank. In the sawmill processing of the sawlogs, the flooring blanks are sawn from the sawlogs, mostly in the radial and tangential direction. For such a purpose, sawlogs from domestic species and foreign species are used. Most dominant in this manner are the hardwood species, although softwood species can be used too. Among the domestic species, the most are beech, oak, acacia, elm, ash, and from the softwood species pine and larch.The paper focuses on the maximum quantitative yield of beech and oak sawlogs intended for processing into parquet blanks. The sawing was conducted on a bandsaw. The blanks were with a thickness of 25,0 mm. The sawlogs belonged to the I, II, and III quality classes. A total of 12 sawlogs were processed, 6 from beech (Fagus sylvatica L.) and 6 from oak (Quercus robur). All sawlogs were with a constant length of 3,0 m. The mean diameter for beech and oak sawlogs was in the range of 34,0 to 36,0 cm.The average value for the quantitative yield for beech sawlogs from I, II, and III quality classes was 37,90%. For the oak sawlogs from I, II, and III quality classes the average value of the quantitative yield was 39,40%.